- From Problematic Village To Thematic Village. Effort To Erase The Negative Image Of Kampung Kuningan Semarang 1995-2017: Dari Kampung Problematik Menjadi Kampung Tematik. Upaya Menghapus Citra Negatif Kampung Kuningan Semarang 1995-2017 - Dimas Said Fauzan; Nina Witasari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Urban villages are the term for housing or residences of lower-class people in the city. In the city, villages are closely associated with marginalization that grows and develops without normative standards. Villages that are mostly from lower-class communities are often victims of policies, isolated, and even complex about social problems such as slums and crimes committed. One of the villages with these social problems is the Kuningan village located in the city of Semarang. In general, the crimes committed in the Kuningan village form a negative image in the city, the crimes committed are a form of situational crime due to the pressure of fulfilling life's needs. In this study, the main focus is on efforts to eliminate the negative image of the Kuningan village in the city of Semarang in the period 1995-2017. Data collection was carried out by searching for document studies and literature studies. The results of this study provide information about the development of the community and the Kuningan village area of ​​Semarang in dealing with social problems in the period from 1995 to 2017 which has experienced fluctuations in environmental conditions due to both natural and human factors.